THE EFFECT OF BIOLOGICALLY ACTIVE POLYMER PREPARATIONS ON THE ROOTING CHARACTERISTICS OF MULBERRY CUTTINGS UNDER THE CLIMATIC CONDITIONS OF SURKHANDARYA REGION (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
Vegetative propagation of mulberry (Morus) trees is a key factor for increasing cocoon yield and improving silk quality. Biologically active polymer preparations are an effective means of enhancing the rooting ability of cuttings and promoting root system development. In the study, cuttings from the varieties Jarariq-10, Jarariq-9, SANIISH-25, Mustaqillik-18, and Tajik Seedless were treated with the preparation and planted. The results showed that Jarariq-10 and Jarariq-9 exhibited the highest rooting percentages (80% and 76%, respectively) and well-developed root systems, providing a practical basis for vegetative propagation recommendations.
Keywords: Mulberry, cuttings, vegetative propagation, biologically active polymer, root system.